MODERN REHABILITATION APPROACHES ADDICTION - Литвинчук, Л. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Representation of rehabilitation approaches in modern addictology is extremely wide. Currently, there are about five thousand rehabilitation programs in the world. It should be emphasized that the selection criteria for drug-addicted persons’ inclusion into a particular rehabilitation program are almost undeveloped and so far, there is no single, most effective therapeutic tooling and common, most effective therapeutic method of drug addicts’ rehabilitation. This article is intended to reveal modern rehabilitation approaches in addictology. It covers the professional, semiprofessional, religious, traditional, non-professional, therapeutic communities. It is noted that nowadays the most well-known and authoritative of them are the Day-top, Sinanon, Narconon, Monar, Almero, Phoenix, Haus etc. The World Federation of Therapeutic Communities and the International Community Association are functioning successfully. In all the countries their activities are enshrined in the state and state-based regional statutes and codes. These institutions may include special schools, mental hospitals, prison institutions, dormitories, communities, ambulance stations etc. Relevant to rehabilitation process is an achievement motivation concept when aspiration for work is based on the need for achievement, identity and self-security. As a rule, occupational therapy should target the identity of the patient, i.e. the work should be meaningful and evoke the sense of responsibility. According to many experts in the field of rehabilitation, therapeutic communities have proven to be the most effective organizational structure, providing medical, psychological and social assistance to narcological patients. Key words: addictology, rehabilitation approach, rehabilitation program, therapeutic community, substance abuse patient, Minnesota Model, inpatient hospital department, outpatient clinic.